Teatr jednego aktora i czterech ścian - Miksza, Weronika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
This article concerns hikikomori, which is an Asian phenomenon. It discusses this issue from different angles. The countries covered in the article include: South Korea, Japan, China, Singapore and other Asian countries. In addition this paper describes certain features of hikikomori as well as the phenomenon’s origin. The ways in which hikikomori is presented in popular culture are also touched upon here. The conclusion at the end sums up all the key points in one paragraph.